Spondylodiscitis in pediatric age – a diagnostic challenge - Ferreira, Joana (2018)
Spondylodiscitis is an inflammatory process of the intervertebral disc and the adjacent vertebral endplates and mainly involves the lumbar spine. Clinical suspicion is not raised in most instances, often resulting in difficult and delayed diagnosis. The onset may be insidious and clinical signs can be mild and unspecific. This is also true with laboratory tests, which often remain within the normal range. Refusal to walk and back pain are the main symptoms, and magnetic resonance imaging of the spine is the gold standard for the diagnosis. The duration and type of treatment are controversial, but the use of antimicrobial therapy together with rest and immobilization showed good results in specific cases, leading to a progressive recovery. We describe a previously healthy two-year old boy with spondylodiscitis, in whom no direct infectious pathogen was identified. We discuss the clinical features, laboratory findings, as well as the outcome of this clinical entity based on a review of the reported cases